A throughput method using the quick easy cheap effective rugged safe method for the quantification of ibuprofen and its main metabolites in soils - Paíga, Paula (2016)
Quick, easy, cheap, effective, rugged, and safe extraction is a modern sample preparation method that involves a number of steps with a low susceptibility to error. The efficiency of a laboratory can be improved not only through labor reduction and consumable savings but also through the use of high-throughput methods and the reduction of wastes. In commercially available kits, different salts and buffers are mixed in anhydrous packages. The composition of these kits are optimized and fixed for particular applications by the suppliers. In this work three model compounds (ibuprofen and two of its main metabolites: hydroxyibuprofen and carboxyibuprofen) were chosen and the amount of each salt (magnesium sulfate, sodium chloride, sodium citrate, and disodium citrate sesquihydrate) in the quick, easy, cheap, effective, rugged, and safe content was optimized for three different soil samples (soils A, B, and C) with different organic carbon contents, using a 24 factorial design. The optimized extraction procedure was applied to 12 soil samples; ranging from river sediments to agricultural soils. Based on the analysis 100 samples, a price reduction of 5.1- (soil B), 5.7- (Soil C), and 6.1-fold (soil A) was achieved without compromising the performance of the method when compared to commercial kits.